(untitled) (Global Journal of Human-Social Science, 2020)
e-Government or digital government has emerged as the innovation of the 21st century. Both advanced and emerging countries are modernizing and transforming their administrative systems through the use of internet. The benefits of digital government are enormous and it includes greater accountability of the government, increases efficiency, reduces cost, and improves the standard of living for global citizens. However, e-Government in developing countries is still pose with implementation challenges and these have led to massive e-Government project failures. An adaptation model from DeLone and McLean’s Information System (IS) success model is developed and proposed as an alternative for e-Government success in Africa. The results of this study show that political and bureaucratic commitment, economic development, right policies, participation in e-Services, and socio-cultural development are sufficient or necessary factors for e-Government development in Africa. Policy recommendation for e-Government development in Africa is also highlighted.